Technological features of Ti–Cr–B–N coatings formation by magnetron sputtering method in a direct current - S. D. Latushkina; I. M. Romanov; A. R. Luchenok; O. I. Posylkina; Yu. A. Harlan; Ya. Yu. Martinkevich (Литьë и металлургия, 2019)
The results of the study of the phase composition and physical and mechanical properties of multicomponent coatings Ti– Cr–B–N formed by magnetron sputtering at a constant current from composite targets are presented. The features of phase formation of coatings when spraying targets containing titanium diboride (TiB2) or boron nitride (BN) as a boron-containing component are studied. The conditions of deposition of coatings with microhardness up to 32 GPA and heat resistance up to 800 °C are established.